IL novecento Argentino. Migration and suburban dialects - Salazar, Mauro (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
As a scriptural text (Barthes), our passages do not seek the progression of an argument, but its "reiteration" in different discursive moments and visual narratives that are illuminated by temporalities. The above invokes fragments of urban-realistic literature, as well as essays and research on dialects and immigration, to account for the complex physiognomy of the city of Buenos Aires and the avatars of the State under the Argentine Centenary (1910). In such a cultural climate, institutional discourses promoted "archives" of urbanization and territorial regulation to build a social pact, which had to deal with "peripheral speech", practices of uprooting and imposing an economy of bodies. Finally, the oligarchy -of Parisian vocation- normalized discourses and migrant practices implementing a crusade against the immorality of the aesthetic porteñas, namely, conventillos, brothels, suburbs, suburbs and the "epidemiological tango" that deformed the future of the port city.